Which early risk factors should be used to identify a baby's risk of obesity? The BERTIE project. (24th May 2012) - Willis, TA; Phillips, RS; Dahly, D; Levine, R; Rudolf, MCJ
Abstract : Aims: With one in four children starting school overweight, prevention needs to start in the preschool years. BERTIE (Babies and Early-years Risk: Trying to Implement the Evidence) aims to help health professionals identify babies at risk of obesity to provide appropriate guidance. Methods: Systematic review of the effect of selected perinatal factors associated with later obesity. The GRADE (Grading of Recommendations, Assessment, Development and Evaluation) method was used to evaluate and synthesise the evidence and rate the quality of evidence for recommendations. A consensus meeting of experts debated the findings and their suitability. Results: The consensus meeting identified maternal obesity, infant weight centile, infant weight gain, and smoking in pregnancy as the factors that would be most helpful in identifying infants at the greatest risk of later obesity. Socioeconomic status and ethnicity merited further exploration, though it was recognised that usefully measuring these factors would present challenges. Evidence relating to the other factors (birth weight, diabetes in pregnancy, infant sleep pattern, breastfeeding and weight gain in pregnancy) was not considered strong enough to suggest they would be useful perinatal predictors of later obesity risk. Conclusion: These findings provide guidance for how families might be targeted for obesity prevention. Given the importance of parental obesity, training health professionals to sensitively engage with families is needed to ensure those at high risk receive the intervention required.